2016
DOI: 10.7860/jcdr/2016/21702.9050
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prophylactic Tranexamic Acid in Reducing Blood Loss during Elective Caesarean Section: A Randomized Controlled Stud y

Abstract: INTRODUCTIONEvery year over five lac women die worldwide due to causes related to pregnancy and delivery. Postpartum Haemorrhage (PPH) accounts for the major part of the mortality as well as morbidity like severe anaemia, need for blood transfusion, hospital stay and infection. Millennium Development Goal 5 targets for reduction of maternal mortality rate by 75% by 2015, which means 5.5% reduction per year is required. People at high risk of PPH account for only small percent of all maternal deaths. Majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…A recent meta‐analysis of nine trials involving 2365 patients confirmed these findings, demonstrating that the administration of tranexamic acid before cesarean delivery significantly reduces intra‐ and postoperative blood loss and blood transfusion with no increase in thromboembolic events . After this analysis, three more placebo‐controlled trials have shown that tranexamic acid administration immediately before cesarean delivery significantly reduces reported intraoperative blood loss and postoperative declines in hemoglobin without any increase in adverse maternal or neonatal effects …”
Section: Intraoperative Considerationsmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent meta‐analysis of nine trials involving 2365 patients confirmed these findings, demonstrating that the administration of tranexamic acid before cesarean delivery significantly reduces intra‐ and postoperative blood loss and blood transfusion with no increase in thromboembolic events . After this analysis, three more placebo‐controlled trials have shown that tranexamic acid administration immediately before cesarean delivery significantly reduces reported intraoperative blood loss and postoperative declines in hemoglobin without any increase in adverse maternal or neonatal effects …”
Section: Intraoperative Considerationsmentioning
confidence: 86%
“…48 After this analysis, three more placebocontrolled trials have shown that tranexamic acid administration immediately before cesarean delivery significantly reduces reported intraoperative blood loss and postoperative declines in hemoglobin without any increase in adverse maternal or neonatal effects. [49][50][51] No trials have specifically examined the role of tranexamic acid in the surgical management of PAS disorders. However, the quality of the evidence on postpartum hemorrhage justifies its use in the management of women diagnosed prenatally or presenting with PAS disorders at the time of delivery.…”
Section: Tranexemic Acidmentioning
confidence: 99%
“…It is a known fact that there is release of coagulant factors as well as rapid degradation of fibrinogen and fibrin during placental delivery owing to vascular injury. 20 These physiological events increase fibrinolysis which can last for several hours postpartum. What complicates the matter in CS delivery is the fact that extensive tissue injury caused by the operative procedure contributes further to this process of increased fibrinolysis and resultant bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in accordance with others where only 3.33% women of study arm had this much amount of blood loss in comparison to 60% of the control group (which was 18% in the present study). 20 Cochrane review published promising results for decreased mean blood loss of greater than 500 mL to be more apparent with vaginal births whereas blood loss greater than 1000 mL was decreased with the use of TXA in caesarean section. 7 Moreover in a meta analysis, the mean total blood loss during and after CS was significantly less in TXA group than in control group having a mean difference of 141.61 mL with 95% confidence interval (CI) of 207.09 − 76.14 (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation